Determination of ligand-binding specificity by alternative splicing: two distinct growth factor receptors encoded by a single gene. - Miki, T (1992)
Expression cDNA cloning and structural analysis of the human keratinocyte growth factor receptor (KGFR) revealed identity with one of the fibroblast growth factor (FGF) receptors encoded by the bek gene (FGFR-2), except for a divergent stretch of 49 amino acids in their extracellular domains. Binding assays demonstrated that the KGFR was a high-affinity receptor for both KGF and acidic FGF, while FGFR-2 showed high affinity for basic and acidic FGF but no detectable binding by KGF. Genomic analysis of the bek gene revealed two alternative exons responsible for the region of divergence between the two receptors. The KGFR transcript was specific to epithelial cells, and it appeared to be differentially regulated with respect to the alternative FGFR-2 transcript. Thus, two growth factor receptors with different ligand-binding specificities and expression patterns are encoded by alternative transcripts of the same gene.